2015
DOI: 10.1007/s40519-014-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, health-related quality of life and economic burden of binge eating disorder: a systematic literature review

Abstract: PurposeTo perform a systematic review on the epidemiology, the health-related quality of life (HRQoL) and economic burden of binge eating disorder (BED).MethodsA systematic literature search of English-language articles was conducted using Medline, Embase, PsycINFO, PsycARTICLES, Academic Search Complete, CINAHL Plus, Business Source Premier and Cochrane Library. Literature search on epidemiology was limited to studies published between 2009 and 2013. Cost data were inflated and converted to 2012 US$ purchasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 54 publications
3
63
0
5
Order By: Relevance
“…Binge eating disorder (BED) is the newest defined and most frequent eating disorder with a significant mental burden and a high comorbidity with obesity and subsequent somatic diseases [1]. The main criterion of BED according to DSM-5 [2] is the occurrence of binge eating (BE) episodes, at least once a week in 3 months, accompanied by a subjective loss of control.…”
Section: Introductionmentioning
confidence: 99%
“…Binge eating disorder (BED) is the newest defined and most frequent eating disorder with a significant mental burden and a high comorbidity with obesity and subsequent somatic diseases [1]. The main criterion of BED according to DSM-5 [2] is the occurrence of binge eating (BE) episodes, at least once a week in 3 months, accompanied by a subjective loss of control.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pathological eating is increased in patients with obesity seeking bariatric surgery [4,20]. Particularly, the diagnosis of a binge eating disorder (BED) in patients who wait for bariatric surgery, with a point prevalence of 13.4% and 14.6% of subthreshold binge eating, is remarkably high [21], compared with the lifetime prevalence of 1.1%–1.9% in the general population [22]. Concerning the impact of the affective state , several studies indicate that people with obesity show pathological eating behavior especially in negative mood [23], which is in line with the negative urgency concept of impulsivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another study drawn from the same population showed an independent increased risk of irritable bowel syndrome and gastroesophageal reflux disorder (GERD) [29]. Overall health-related quality of life in binge eating patients is significantly lower than noneating disorder patients and physical health-related quality of life in the BED group is lower than that of other eating disorder groups [30].…”
Section: Specify Ifmentioning
confidence: 99%